Preference reversal in intertemporal decision making - Zhou, Yan-Bang; Zhang, Kun; Zhai, Hong-Kun; Bao, Qing; Xiao, Shanshan; Dang, Junhua (Frontiers in Psychology, 2024)
This study investigates asymmetric preference reversals in intertemporal decisionmaking, comparing gain and loss contexts across choice and bidding tasks. Findings reveal that in gain scenarios, participants favored smaller, sooner (SS) rewards in choice tasks but valued larger, later (LL) rewards in bidding tasks. Conversely, in loss scenarios, they preferred LL options in choice tasks but bid lower on SS options. The bidding task, which consistently took more decision time than the choice task, suggests heightened cognitive demands during valuation, indicating that task formats significantly impact preference formation. Complementing these findings, a real-world questionnaire validated preference reversal patterns across economic and health scenarios, reinforcing the study's practical implications for consumer behavior, financial decision-making, and policy design. This research highlights the influence of response modes on preference, offering insights for interventions that align more closely with individuals' underlying preferences.